Word frequency cues word order in adults: cross-linguistic evidence - Gervain, Judit; Sebastian-Galles, Nuria; Diaz, Begona; Laka, Itziar; Mazuka, Reiko; Yamane, Naoto; Nespor, Marina; Mehler, Jacques (Frontiers in Psychology, 2013)
One universal feature of human languages is the division between grammatical functors and content words. From a learnability point of view, functors might provide entry points or anchors into the syntactic structure of utterances due to their high frequency. Despite its potentially universal scope, this hypothesis has not yet been tested on typologically different languages and on populations of different ages. Here we report a corpus study and an artificial grammar learning experiment testing the anchoring hypothesis in Basque, Japanese, French and Italian adults. We show that adults are sensitive to the distribution of functors in their native language and use them when learning new linguistic material. However, compared to infants’ performance on a similar task, adults exhibit a slightly different behavior, matching the frequency distributions of their native language more closely than infants do. This finding bears on the issue of the continuity of language learning mechanisms.